2020
DOI: 10.3389/fphar.2020.01233
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Eicosanoids in Gynecological Malignancies

Abstract: Eicosanoids, bio-active lipid molecules, evoke a multitude of biological effects that directly affect cancer cells and indirectly affect tumor microenvironment. An emerging role has been shown for eicosanoids in the pathogenesis of gynecological malignancies which include cancers of the vulva, vagina, cervix, uterine, and ovary. Eicosanoid biosynthesis pathways start at the metabolism of phospholipids by phospholipase A2 then proceeding to one of three pathways: the cyclooxygenase (COX), lipoxygenase (LOX), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 189 publications
0
2
0
Order By: Relevance
“…The cyclooxygenase-2 (COX-2)/prostaglandin E2 (PGE2) axis is a crucial modulator of low-grade chronic inflammation, orchestrating the inflammatory characteristics of the TIME and contributing to the development and progression of diverse cancers [ 17 , 18 , 19 , 20 , 21 ]. The COX-2/PGE2 axis is an inducible inflammatory signaling cascade in response to numerous inflammatory mediators (i.e., tumor necrosis factor-alpha (TNF-α), IL-6, among others), oncogenes, and growth factors [ 18 , 22 ]. Multiple studies indicated significant activity of the COX-2/PGE2 axis in the TIME of HGSOC, the expression of which promotes the malignant behavior of ovarian cancer cell lines [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cyclooxygenase-2 (COX-2)/prostaglandin E2 (PGE2) axis is a crucial modulator of low-grade chronic inflammation, orchestrating the inflammatory characteristics of the TIME and contributing to the development and progression of diverse cancers [ 17 , 18 , 19 , 20 , 21 ]. The COX-2/PGE2 axis is an inducible inflammatory signaling cascade in response to numerous inflammatory mediators (i.e., tumor necrosis factor-alpha (TNF-α), IL-6, among others), oncogenes, and growth factors [ 18 , 22 ]. Multiple studies indicated significant activity of the COX-2/PGE2 axis in the TIME of HGSOC, the expression of which promotes the malignant behavior of ovarian cancer cell lines [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…EP4 is a G protein-coupled receptor that contributes to cancer progression and metastasis by promoting cancer cell invasion and migration, inducing tumor-associated angiogenesis, and attenuating the anti-cancer immune response [ 17 , 18 , 19 ]. EP4 is implicated in the onset and progression of numerous cancers including ovarian, lung, breast, uterine, colorectal, cervical, and prostate, among others [ 19 , 20 , 21 ]. A study by Spinella et al showed that EP4 activation stimulates vascular endothelial growth factor (VEGF) production, cell migration, and matrix metalloproteinase activity in HEY human ovarian cancer cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%